Implementation Of The Dempster Shafer Method For The Diagnosis Of Sepsis - Tara Aprilinda; Siswanto Siswanto; Yupianti Yupianti (Jurnal Komputer, Informasi dan Teknologi, 2023)
Sepsis is a disease that starts from infection. When an infection occurs, the body's organ systems will be damaged because when the blood flow is filled with chemical compounds produced by the body with the aim of fighting infection and triggering an inflammatory response that is damaged in the function of the body's organs, causing important organs to fail in working so that it leads to death. People often do not realize that the disease they suffer has reached the sepsis stage. Since sepsis is a rare disease and difficult to find an expert, a tool is designed to use an expert system to diagnose sepsis early from the symptoms felt by the user. This expert system was designed using the PHP Programming Language and MySQL database by implementing the Demster Shafer Method. The expert system created can make it easy for users to consult about Sepsis online..